Digital Leadership in Organization: Systematic Literature Review - Woro, Ludita; Herachwati, Nuri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study conducts a systematic review of digital leadership in organizations. In the era of digital transformation, digital leadership is increasingly important, yet publications on this topic are limited compared to other leadership styles. Through a literature search on Scopus and Web of Science, we selected 24 relevant articles out of 414. Findings indicate an increasing trend in publications since 2016. Selected articles cover definitions, perspectives, research designs, and outcomes. Digital leadership combines leadership practices and technology. However, the definition of digital leadership still varies. Most studies use a quantitative approach with questionnaires. This study provides a comprehensive understanding of digital leadership and identifies knowledge gaps for future research. The article contributes to practitioners and academics understanding of digital leadership in the era of digital transformation.